2022
DOI: 10.1080/15502783.2022.2036436
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intakes, Knowledge, and Perceptions of Semi-professional Rugby Athletes in Scotland

Abstract: Background Adequate nutritional intake plays a pivotal role in optimizing performance, recovery, and body composition goals. This study aimed to investigate the dietary intakes (DIs); nutritional knowledge (NK); and attitudes, perceptions, and challenges (APC) of semiprofessional rugby players in Scotland. Methods Dietary intakes and NK of 24 male semiprofessional rugby players of a Super6 club were evaluated using validated questionnaires. Players were categorized as h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…These protein intakes and the values modeled in the present study reside within the range reported in surveys of the dietary intakes of rugby players, which indicate mean protein intakes of 1.02-2.59 g/kg [8,10,22,23,72,77]. These values may reflect larger intakes of protein supplements, the use of which is prevalent among rugby players [71,[78][79][80]. In contrast, dietary data modeled from the AHS-2 cohort included limited capture of meal replacement drinks and protein supplements, where the top reported sources of protein included legumes, grains, and other whole plant foods [81].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These protein intakes and the values modeled in the present study reside within the range reported in surveys of the dietary intakes of rugby players, which indicate mean protein intakes of 1.02-2.59 g/kg [8,10,22,23,72,77]. These values may reflect larger intakes of protein supplements, the use of which is prevalent among rugby players [71,[78][79][80]. In contrast, dietary data modeled from the AHS-2 cohort included limited capture of meal replacement drinks and protein supplements, where the top reported sources of protein included legumes, grains, and other whole plant foods [81].…”
Section: Discussionsupporting
confidence: 81%
“…A systematic review that used 24 h recalls and food diaries of varying durations to estimate the dietary intakes of team sport athletes including rugby players reported mean energy intakes that ranged from 3177 to 4336 kcal/day [70]. Additional research using FFQ, 24 h recalls, and food diaries estimated the energy intakes of rugby players to be between 2284 and 3875 kcal/day [8,10,22,23,71,72]. Low reported energy intakes relative to TEE have led to observations of a negative energy balance (−1382 kcal/day) in rugby players [10], accompanied by suggestions for cautious interpretation due to underreporting during dietary assessment and limitations in energy intake estimations [10,72].…”
Section: Discussionmentioning
confidence: 99%
“…Comparable findings were reported among elite English squash players (56.1%) and professional athletes in the Australian women’s football league (50.6%) [ 26 , 27 ]. Conversely, studies conducted with professional Irish Gaelic footballers, Australian team sports athletes, and Scottish rugby athletes revealed a poor NK level (<50%) [ 28 , 29 , 30 , 31 ]. Similar to the current study, no correlation was demonstrated between age, educational level and the level of NK in the athletes [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is proven by research from [8], [22], [32]- [34]. This is caused by a lack of knowledge of athletes and coaches in setting the right athlete's diet [13], [15], [28], [35]. By having good nutritional knowledge, athletes will manage intake appropriately [36].…”
Section: Surveymentioning
confidence: 99%
“…Understanding of consuming proper food intake for athletes is lacking. This is shown through research conducted by [35], [46], [47]. The average athlete has low nutritional knowledge so they consume inappropriate foods.…”
Section: Surveymentioning
confidence: 99%